Interventions to change clinicians' behavior related to suicide prevention care in the emergency department: a scoping review. Issue 3 (13th March 2022) - Shin, Hwayeon Danielle; Cassidy, Christine; Weeks, Lori E.; Campbell, Leslie Anne; Drake, Emily K.; Wong, Helen; Donnelly, Lauren; Dorey, Rachel; Kang, Hyelee; Curran, Janet A.
ABSTRACT: Objective: The objective of this scoping review was to explore, characterize, and map the literature on interventions and intervention components implemented to change emergency department clinicians' behavior related to suicide prevention using the Behaviour Change Wheel as a guiding theoretical framework. Introduction: An emergency department is a critical place for suicide prevention, yet patients are often discharged without proper suicide risk assessments or referrals. In response, we must support emergency department clinicians' behavior change to follow evidence-based suicide prevention strategies. However, reviews to date have yet to systematically and theoretically examine the functional mechanisms of interventions and how these characteristics can influence emergency department clinicians' behaviors related to suicide prevention care. Inclusion criteria: This review considered interventions that targeted emergency department clinicians' behavior change related to suicide prevention. Behavior change referred to observable practice changes as well as proxy measures of behavior change, including changes in knowledge and attitude. Methods: This review followed JBI methodology for scoping reviews. Searches included PubMed, PsycINFO, CINAHL, Embase, and gray literature, including targeted Google searches for relevant organizations/websites, ProQuest Dissertations and Theses Global, and Scopus conference papers (using a specific filter). This review did not apply any date limits, but our search was limited to the English language. Data extraction was undertaken using a charting table developed specifically for the review objective. Narrative descriptions of interventions were coded using the Behaviour Change Wheel's intervention functions. Reported outcome measures were categorized. Findings were tabulated and synthesized narratively. Results: This review included a total of 70 sources, describing 66 different interventions. Forty-one studies were included from the database searches, representing a mixture of experimental (n = 2), quasi-experimental (n = 24), non-experimental (n = 12), qualitative (n = 1), and mixed methods (n = 2) approaches. An additional 29 citations were included from gray literature searches. One was a pilot mixed methods study, and the rest were interventions. Identified interventions comprised a wide range of Behaviour Change Wheel intervention functions to change clinicians' behavior: education (n = 48), training (n = 40), enablement (n = 36), persuasion (n = 21), environmental restructuring (n = 18), modeling (n = 7), and incentivization (n = 2). Based on the Behaviour Change Wheel analysis, many interventions targeted more than one determinant of behavior change, often employing education and training to improve clinicians' knowledge and skills simultaneously. Among the 42 studies that reported outcome measures, effectiveness was measured at clinician (n = 38), patient (n = 4), or organization levels (n = 6). Few studies reported implementation outcomes, such as measures of reach (n = 4), adoption (n = 5), or fidelity (n = 1). There were no evaluation data reported on the interventions identified through Google searches. Conclusions: Interventions included in this review were diverse and leveraged a range of mechanisms to change emergency department clinicians' behavior. However, most interventions relied solely on education and/or training to improve clinicians' knowledge and/or skills. Future research should consider diverse intervention functions to target both individual- and organization-level barriers for a given context. The ultimate goal for changing emergency department clinicians' behavior is to improve patient health outcomes related to suicide-related thoughts and behaviors; however, current research has most commonly evaluated clinicians' behavior in isolation of patient outcomes. Future studies should consider reporting patient-level outcomes alongside clinician-level outcomes.